PHILOSOPHICAL AND HISTORICAL RECONSTRUCTION OF CHINESE AESTHETIC VALUES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the nature of values in general and the semantic meanings of the concept of "aesthetic values" in particular: material-objective, psychological, and social. The transformation of ideas about aesthetic values is examined through the lens of Confucianism and Taoism. The role of system-forming categories in the context of Chinese aesthetic values is substantiated: beauty (mei), the energetic substance of the universe (qi), “wind” (feng), virtue (hao), naturalness (ping), and the "heavenly pattern." The value of Chinese philosophical-aesthetic thought is shown in its ability to offer a cosmic dimension to world perception and to create a new ontology of harmony—of the world with itself and with the Absolute.